The effect of steam learning based on project-based learning (pjbl) assisted by assemblr edu on elementary school students' creative thinking skills - Rezki Ungki Yanna Opsari; Parji; Marheny Lukitasari (Universitas PGRI Madiun, 2025)
Creative thinking is one of the essential 21st-century skills that should be developed in elementary school students to enhance problem-solving abilities and generate innovative ideas. However, preliminary observations in Grade V of SDN Sugihwaras 2 indicated that students' creative thinking skills were still relatively low. This study aimed to examine the effect of Science, Technology, Engineering, Arts, and Mathematics (STEAM) learning based on Project-Based Learning (PjBL) assisted by Assemblr Edu on students' creative thinking skills. A quantitative pre-experimental method with a One-Group Pretest–Posttest Design was employed. The participants were 20 fifth-grade students selected through purposive sampling. Data were collected using a creative thinking test covering fluency, flexibility, originality, and elaboration. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Paired Sample t-test. The findings indicate that STEAM-based Project-Based Learning (PjBL) assisted by Assemblr Edu effectively enhanced elementary school students' creative thinking skills. The integration of project-based activities with immersive augmented reality learning experiences encouraged students to generate original ideas, explore multiple problem-solving strategies, and elaborate their ideas more creatively. These results support the view that authentic, technology-enhanced STEAM learning environments foster higher-order thinking and creativity in elementary education.